Effect of counseling intervention on symptoms, pain acceptance and psychological wellbeing among patients with fibromyalgia - Ayman Muhammad Kamel Senosy; Hoda Sayed Mohamed Abd El Naby; Eman Ahmed Elhaweet; Basma ElAraby El-Feqi (BMC Nursing)
Abstract Background Nurses to assist patients make the best choices in challenging circumstances, counseling is crucial. Patients’ health and quality of life can be enhanced by healthcare providers, particularly nurses, through counseling and educational initiatives. Fibromyalgia is characterized by widespread pain that negatively impacts an individual’s ability to work. People may be able to improve their physical and mental health and accept suffering with the use of nursing counseling methods. Aim This study aimed to investigate the effect of counselling intervention on symptoms, pain acceptance, and the psychological well-being of patients with fibromyalgia. Design A quasi-experimental (study and control group pre/post-test) design included 120 patients with fibromyalgia during their follow-up visits to the outpatient rheumatology clinic at El-Demerdash Hospital affiliated with Ain Shams University Hospitals, Cairo, Egypt. Tools for data collection (1) Structured Interview Questionnaire for Patients with Fibromyalgia, (2) Pain Acceptance Questionnaire, (3) Psychological well-being Questionnaire. Results Post intervention, there were statistically significant differences between the groups in terms of psychological well-being, pain acceptance, and symptoms (p < 0.05). Regarding the total level of pain acceptance post implementation of the counseling intervention, there was a highly statistically significant difference between the study and control groups. Post the implementation of the counseling intervention, there was a statistically significant difference in the study group’s anxiety, depression, vitality, positive well-being, and general health (0.03*, 0.01**). Additionally, the study group’s pain willingness and activity engagement subscales showed statistically significant differences, with a p-value of less than 0.001. Additionally, there were statistically significant differences between the groups pre and post the program’s implementation in terms of psychological well-being, pain acceptance, and symptoms (p < 0.05). Conclusions Patients with fibromyalgia under research report statistically significant improvements in their psychological well-being, pain acceptance, and symptoms when counseling interventions are used. Recommendations In addition to the standard nursing care provided to patients in all fibromyalgia treatment clinics, counseling interventions must be included. Clinics must schedule counseling sessions on a monthly basis. To increase their understanding and boost their mental and physical health, it should be updated on a regular basis. More study is needed to evaluate the biopsychosocial needs of such people and treat all the fibromyalgia-related signs and symptoms. Clinical trial number Not applicable.